2007
DOI: 10.1016/j.cardiores.2007.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of the soluble guanylyl cyclase α1 subunit in vascular smooth muscle relaxation☆

Abstract: We conclude that sGCalpha(1)beta(1) is involved in the vasorelaxation induced by NO-dependent and NO-independent sGC activators in both genders. However, the remaining relaxation seen in the sGCalpha(1)(-/-) mice suggests that besides sGCalpha(1)beta(1) also the minor isoform sGCalpha(2)beta(1) and/or (an) sGC-independent mechanism(s) play(s) a substantial role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 32 publications
2
44
3
Order By: Relevance
“…These findings were supported by previous reports about vasorelaxation induced by NO or NO donors (3,45). Furthermore, the present study also shows that the presence of ODQ, CHT, or BaCl 2 (1 μM) further inhibited relaxations to FLNT, indicating that FLNT activates K Ca and K IR independently of the sGC/ cGMP pathway.…”
Section: Discussionsupporting
confidence: 81%
“…These findings were supported by previous reports about vasorelaxation induced by NO or NO donors (3,45). Furthermore, the present study also shows that the presence of ODQ, CHT, or BaCl 2 (1 μM) further inhibited relaxations to FLNT, indicating that FLNT activates K Ca and K IR independently of the sGC/ cGMP pathway.…”
Section: Discussionsupporting
confidence: 81%
“…Activity of the RAAS modulates endothelium-dependent vascular reactivity. We previously reported that vascular smooth muscle relaxation in response to endothelium-derived NO was severely attenuated in aortic and femoral rings isolated from sGCα 1 -/-S6 mice (19). In an independent study, the ability of acetylcholine to induce vasorelaxation in isolated carotid arteries was attenuated in sGCα 1 -/-B6 mice (27).…”
Section: Figurementioning
confidence: 94%
“…Two isoforms of each subunit have been identified (α 1 , α 2 , β 1 , β 2 ), but only sGCα 1 β 1 and sGCα 2 β 1 appear to function in vivo (16). Although the sGCα 1 β 1 heterodimer is the most abundant sGC isoform in the cardiovasculature (17), low levels of cGMP, generated by sGCα 2 β 1 , are sufficient to mediate many of NO's cardiovascular effects (15,(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the unusual flow patterns seen during the IS superfusion experiments, vasocontractile effect of IS on the vessel was studied using a wire myograph as described by Nimmegeers et al 82 Briefly, three female Wistar rats were used. After cervical dislocation, the thoracic aorta and femoral artery were carefully removed from each animal and transferred to cooled Krebs-Ringer bicarbonate (KRB) solution.…”
Section: Studies Of Vasoactive Effect Of Is In Vitromentioning
confidence: 99%